(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the didactic significance of pedagogical dialogue in developing critical-operational communication in the context of teaching the discipline "Medical Radiology." The author views pedagogical dialogue not merely as a means of knowledge transmission but as a key mechanism for fostering critical thinking, prompt decision-making, and professional communicative competence. The paper substantiates the didactic conditions necessary for cultivating critical-operational communication through the use of case scenarios, visual analysis, problem-based tasks, and elements of debate within the educational process. Furthermore, it emphasizes the need to revise the traditional structure of lessons, create an active communicative environment, and foster students’ skills in reflective analysis.